Development of High-Calcium Chicken Nuggets Fortified with Various Citric Acid - Extracted Chicken Eggshells Powder - Suryono Suryono; Hutwan Syarifuddin; Jesayas Maranata; Musyid Musyid; Addion Nizori (Journal of Applied Agricultural Science and Technology, 2023)
Chicken nuggets are ready-to-eat frozen processed meat products that are ground, steamed, molded, coated, frozen, and fried. Because chicken nuggets have a low calcium content, it must be done with the addition of chicken eggshells powder. Chicken eggshells powder contains natural calcium in the form of calcium carbonate. The current study aims to develop nuggets fortified with citric acid- extracted chicken eggshells powder. The purpose of this research was to determine the effect of fortified calcium citrate from chicken eggshells powder on the physicochemical properties of nuggets. This study used a completely randomized design with 6 treatment levels of chicken eggshells addition: 0%, 1%, 2%, 3%, 4% and 5%, replicated 3 times, so and 18 experimental units. Parameters observed were physico-chemical properties; moisture content, pH, protein and calcium content. The results showed that the citric acid extracted eggshell powder had a significant effect on moisture content, pH, protein content and calcium content of chicken nuggets. The best treatment was the addition of 3% eggshell powder with moisture content of 58.83%, pH value of 6.49, protein 17.23%, and calcium content of 129.99 mg/100g. It is recommended that further research can be conducted to investigate the effect of adding shell calcium on the quality and shelf-life of chicken nuggets during storage with various packaging and temperatures.